L-shaped association between dietary zinc intake and the risk of developing cardiovascular disease in Chinese adults: A cohort study - Zhang, Huanxiang; Wang, Shanjie; Gu, Xia; Qiu, Hongbin; Zhang, Yiying (Frontiers in Nutrition, 2023)
Background: Although the association of zinc (Zn) with cardiovascular disease (CVD) has been studied, no consensus has been reached on this relationship, particularly dietary Zn intake. The purpose of this study is to access the effect of dietary Zn intake on the risk of CVD and to analyze whether this effect varied according to zinc consumption using representative data from China. Methods: 11,470 adults from China Health and Nutrition Survey (CHNS) were eventually enrolled. The dietary information was collected by the 3 day 24-hour dietary recalls combined with dietary weighting method. CVD was defined as participants with self-reported physician-diagnosed apoplexy and/or myocardial infarction during the follow-up. Cox regression was used to calculate the risk of CVD incidence with 95% confidence intervals. Restricted cubic spline function plus Cox regression was used to visualize the influence trend of dietary Zn intake on new-onset CVD and test whether this trend is linear. 2-segment Cox regression was established to address the nonlinear trend. Results: 431 participants developed CVD, including 262 apoplexies and 197 myocardial infarctions. Compared with the lowest quintile (Q1), the adjusted hazard ratios (HRs) and 95% confidence interval (CI) of CVD in Q2 to Q5 of dietary Zn intake were 0.72 (0.54, 0.97), 0.59 (0.42, 0.81), 0.50 (0.34, 0.72) and 0.44 (0.27, 0.71), respectively. The influence trend of dietary Zn intake on new-onset CVD was nonlinear and L-shaped. When dietary Zn intake < 13.66 mg/day, increased dietary Zn intake was significantly associated with decreased risk of developing CVD (HR = 0.87, 95% CI: 0.82–0.92, P-value < 0.0001). Conclusions: An L-shaped trend was observed between dietary Zn intake and the risk of developing CVD, indicating that dietary Zn intake should be improved moderately, but not excessively, for the benefit of cardiovascular disease.